Firm investment and bank health: evidence from Malaysian listed firms. - Masturah Ma'in; Abdul Ghafar Ismail; Abu Hassan Shaari Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper examines the impact of bank financial health on firm investment. The firm-level data are obtained from firms that were listed on Bursa Malaysia between 2000 and 2007. This paper aims to provide additional empirical envidence based on an original paper by Fukuda, Kasuya and Nakajima(2005).This paper also extends the previous literature by using unbalanced panel data methodology. In order to have a robust result, the GLS estimation method is used instead of OLS. In measuring the bank health, this study uses the core capital ratios (CCR) risk weighted capital -adequacy ratios (RWCR)and non-performing loans (NPL) figures. The findings indicate that: first CCR and RWCR have positive impact on investment by firms. The possible explanation is that when CCR and RWCR deteriorate bank lending is reduced: resulting in reduced investment of firms.Second, NPLs have positive impact on firm investment. When banks NPL are low due to government interventions during the Asian financial crisis, investment of firms also deteriorate due to falling aggregate demand. Third, financial variables have positive impact on firm investment, This finding is consistent with previous empirical evidence which suggests that a firm is likely to have a larger investment when it has good investment opportunities.